È già politica. Protoelementi visivi per l'autodeterminazione - Simona La Neve (Ocula)
The visual dimension related to Self realisation in art history, is analyzed as answer to control over the individual. This is verifiable both in the avanguardie and neoavanguardie period where takes place the rewriting of linguistic codes, meaning cultural refusal of oppression. In this essay the visual alphabetical letter is related to the rethinking of the subordinate subject theme, aiming to include postcolonial and extra-artistic reflections.